2009
DOI: 10.1093/jaoac/92.2.538
|View full text |Cite
|
Sign up to set email alerts
|

Application of Graphitized Carbon Black to the QuEChERS Method for Pesticide Multiresidue Analysis in Spinach

Abstract: A modified QuEChERS method was optimized to determine 66 pesticide residues in spinach using gas chromatography with mass spectrometric detection in selected-ion monitoring mode. Graphitized carbon black (GCB) at different levels (0, 5, 10, 15, 20, and 25 mg) was used to adsorb the pigments in spinach extracts. Best recoveries with less colored extract samples for all pesticides analyzed were obtained in the presence of 10 mg GCB. Under the optimized condition, analyses of spiked samples were performed at 3 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…Thus, in Test 2 we incorporated 0.3 g GCB since GCB had previously been shown to remove colored plant pigments from extracts during SPLE [16]. We also used less GCB has been used to reduce pigments in other extraction techniques and has commonly been used in QuEChERS [16,[18][19][20][21][22]. In a previous study, the removal of the pigment β-carotene was monitored using UV spectra and the GCB successfully removed more than 90% of β-carotene from extracts [18].…”
Section: Optimizing the Layered Ase Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in Test 2 we incorporated 0.3 g GCB since GCB had previously been shown to remove colored plant pigments from extracts during SPLE [16]. We also used less GCB has been used to reduce pigments in other extraction techniques and has commonly been used in QuEChERS [16,[18][19][20][21][22]. In a previous study, the removal of the pigment β-carotene was monitored using UV spectra and the GCB successfully removed more than 90% of β-carotene from extracts [18].…”
Section: Optimizing the Layered Ase Methodsmentioning
confidence: 99%
“…While pigments have a strong affinity for GCB, some common target analytes also have an affinity for GCB. Several studies have noted that the use of more GCB leads to a reduction in extraction efficiencies for certain analytes, but for other analytes the GCB has no effect [18,20,21,23].…”
Section: Optimizing the Layered Ase Methodsmentioning
confidence: 99%
“…application should be varied depending on the crop because it may reduce the recovery [29]. In a study on the determination of broflanilide and its two metabolites in five soils, An et al [8] found that GCB mixed with another adsorbent was more effective for purification than only C 18 or PSA.…”
Section: Plos Onementioning
confidence: 99%
“…PSA eliminates polar organic acids, polar pigments, sugars, and fatty acids from the extract. Non polar substances, such as lipids, are attracted by C18, and non‐polar pigments and sterol are adsorbed by GCB .…”
Section: Introductionmentioning
confidence: 99%